Urgensi Kepemimpinan Transformasional Kepala Madrasah Dalam Peningkatan Kinerja Dan Mutu Pendidikan Madrasah Ibtidaiyah Darul Ulum PP Banyuanyar Poto’an Daya Palengaan Pamekasan - A. Shaleh; Taufiqurrahman; Fauzan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aimed to find out the form of leadership, duties, and roles of the principal of Madrasah Ibtidaiyah (The Islamic Elementary School) at Pondok Pesantren Darul Ulum Banyuanyar, Potoan Daya,Palengaan Pamekasan. This educational institution is one of the formal schools in this boarding house. Most students at this school live at the Banyuanyar Islamic boarding house, although some still go from their respective houses (callednyulokin Madurese). The research used a qualitative descriptive method. The data were collected through observation, interviews, and documentation. And to find out the validity of the data, several methods were carried out, such as extending observations, increasing research, and ensuring triangulation. This studyfound that the leadership of the head of Madrasah Ibtidaiyah(MI) Darul UlumBanyuanyar was democratic in nature as a policy holder in the organization.He did not act on his own will. Every action he made always prioritized a joint decision. In his program, the head of MI Darul UlumBanyuanyar often carried out control, supervision, guidance, and protection for his subordinates. Supervision was actualized to the head of the teachers so that teachers could have innovations in teaching to ensure students could have a better level of learning development. As an organizational manager, he provides control to all staff and madrasah managers. Besides, he provides protection for all teachers. Interestingly, the head of MI Darul Ulum Banyuanyar prefers to be called a servant in his organization, a servant who serves all the needs of his subordinates, from the managers to the students who are targets in the organization he is leading